2015
DOI: 10.1007/s13762-015-0908-9
|View full text |Cite
|
Sign up to set email alerts
|

Impregnation of polyurethane foam with activated carbon for enhancing oil removal from water

Abstract: To enhance the oil sorption capacity of polyurethane foam, different amounts of activated carbon (0.5, 1, 2 and 3 wt%) were grafted onto the surface of polyurethane foam. The modified polyurethane foam was characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, thermogravimetric analysis and tensile elongation test. Grafting of activated carbon improved the polyurethane foam toughness and thermal resistance as revealed by tensile elongation and thermogravimetric tests, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…It was also reported that activated carbon prepared from olive stones gave the highest sorption capacity for diclofenac from aqueous solutions, with maximum sorption at pH 2 . However, activated carbon applications are limited because of their poor mechanical strength, low sorption capacity, low selectivity, and incomplete regeneration . Thus, hypercrosslinked (HXL) polymers become interesting as SPE sorbents since they have high specific surface areas (above 1000 m 2 g −1 ) and tuneable chemistry, in combination with a high micropore content .…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that activated carbon prepared from olive stones gave the highest sorption capacity for diclofenac from aqueous solutions, with maximum sorption at pH 2 . However, activated carbon applications are limited because of their poor mechanical strength, low sorption capacity, low selectivity, and incomplete regeneration . Thus, hypercrosslinked (HXL) polymers become interesting as SPE sorbents since they have high specific surface areas (above 1000 m 2 g −1 ) and tuneable chemistry, in combination with a high micropore content .…”
Section: Introductionmentioning
confidence: 99%
“…Table shows a comparative study of the oil sorption for several polyurethane foams. Modification of the foams, as seen in some studies in the literature, is important for improving the oil sorption capacity, but it has some disadvantages, such as increasing the final cost of the material and generating substantial waste, which may hamper the large‐scale production of adsorbent materials. Therefore, this work is justified by the attempt to produce polyurethane foams that have good sorption capacity through balance of stoichiometric of additives that influence the physical and chemical properties of the material without any further chemical modification of the finished product.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there are various functional groups in the polyurethane foam structures (urethane, amide, ester, ether, urea, etc.) that allow for chemical modification of polymer …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the fish scale was dried and ground to fine powder it was necessary to provide physical support and increase the accessibility of the metal binding sites for process applications. The adsorption capacity of chitosan was increased by impregnated on polyurethane foam [16][17][18][19][20][21][22][23] , hence the similar base material was tested here for the dry powder of waste fish scale. In this work removal and recovery of hazardous metals such as Zn (II), Cu (II), Cd(II), Pb(II), Fe(II) and Mn(II) in industrial effluent using waste fish scale powder impregnated polyurethane foam was studied.…”
Section: Introductionmentioning
confidence: 99%